Remote Monitoring System for a Photovoltaic Power Substation - Wenxing, Wang (International Journal of Online and Biomedical Engineering (iJOE), 2015)
After briefly analyzing the structure of a photovoltaic power substation monitoring system, a positioning system roadway based on blue tooth was put forward to connect with already existing communication and monitoring networks. A separate monitoring system for the environment is integrated with the former comprehensive automation system to create a unique system. It is a new step of substation automation. The system architecture, software, hardware, and necessary factions of this system are introduced in detail. In photovoltaic power substation tunnels, monitoring identity code terminal stations are set along the power line information to collect personnel information data by receiving wireless signals.